The Debtor’s Behavior in Microfinance Industry: An Exploratory Study of Measurement Scales - Susanto, Joko; Raharja, Bayu Sindhu (Jurnal Analisis Bisnis Ekonomi, 2020)
This study is an exploratory descriptive research that attempts to explore the measurement indicators of debtors’ behavior in microfinance industry. It employs as much of previous studies showed little attention in the relation of debtor's behaviour and non-performing loans. On the contrary, they spotlight more on the banking-specific information and macroeconomics factors. Therefore, this research tries to discover the debtor's behaviour which is assumed to have an impact on non-performing loans. The behaviours which employed and proposed are impulsiveness, risk-taking behaviour, and trustworthiness. This study aims to inquiry the measurement scales of proposed behaviours as well as test the validity and reliability of those indicators by employing exploratory factor analysis (EFA). The result shows that there are three indicators accepted being a measuring instrument of impulsiveness, two for risk-taking behaviour, and four signs for trustworthiness. It also examines in the descriptive analysis of the debtor's behaviour based on their socio-demographic criteria such as gender, age, marriage status, and wage. The research result would give an insight into both empirical and practical advantage in terms of microfinancing management. Theoretically, this paper serves a valid and reliable of debtors’ behavior measurement scales that would contribute for future research in testing the relation of such behavior variables to non-performing loans.